Optimal indoor heat distribution: Virtual heaters - Léger, Jérémie; Rousse, Daniel R.; Lassue, Stéphane (Applied energy, 2019)
•A new method for investigating indoor heat distribution is introduced.•New performance indices are defined using the new method (virtual heaters).•Optimal heat distribution can be found without any technological biases.•A case study demonstrates how to apply the virtual heaters. It is well known that indoor heat distribution can affect energy consumption according to the thermal comfort of the occupants. While most work on this topic has focused on specific heaters and how they distribute heat, this paper proposes a new concept termed virtual heaters. Virtual heaters are a set of two optimized heat distributors that respectively maximize and minimize the energy consumption inside a room while maintaining the same level of thermal comfort. The maximum and minimum virtual heaters are then applied in a comparison with a real heater tested in a specific room at constant thermal comfort in order to quantify its ability to provide comfort while using a minimum amount of energy. To calculate the ”virtual heaters”, a simplified heat transfer model is formulated and implemented. A volumetric thermal comfort model using the predicted mean vote is also discussed and used. The ”simplified” heat transfer model with the thermal comfort constraint is then optimized via a sequential quadratic programming algorithm. The proposed method is applied to the heating of a room subject to an outdoor temperature of -20°C and compared to experimental results. Results show that the maximum virtual heater consumes approximately 35% more energy than the minimum virtual heater for the case considered herein.